Yielding capacity and regeneration of different ages fruit-bearing shoots in sour cherry - Gonda, I.; Such, Z. (International Journal of Horticultural Science, 2008)
The yielding potential and regeneration (i.e. germination of hidden buds) after pruning of the fruit-bearing shoots of different ages were compared in sour cherry cultivars pruned to spindle shape. The examinations were carried out in order to determine the optimal pruning strategy resulting in the highest long-term yielding of sour cherry cultivars with intensive crown shape (free and thin spindle shape). According to our results, there are great differences among the studied self-fertile sour cherry cultivars in yielding and regeneration, which are worthwhile to be considered in determining the method and degree of pruning.